Clinical Significance of Respiratory Involvement in Cryptosporidiosis: Cross-Sectional Study of Children with Diarrhea and Respiratory Symptoms in Uganda - Mor, Siobhan M; Ndeezi, Grace; Ascolillo, Luke R; Tasimwa, Hannington B; Attipa, Charalampos; Sponseller, Jerlyn; Mukunya, David; Nakato, Ritah; Kayondo, Lilian N; Tzipori, Saul; Tumwine, James K; Griffiths, Jeffrey K (My University, 2024)
Respiratory cryptosporidiosis is considered an occasional, late-stage complication of HIV/AIDS. This study aimed to assess the clinical importance of respiratory cryptosporidiosis in children with diarrhea and respiratory symptoms at Mulago Hospital, Kampala, Uganda. Children aged 9 to 36 months presenting with diarrhea and cough or unexplained tachypnea (N = 1,918) were screened for fecal Cryptosporidium using polymerase chain reaction (PCR). Children with positive stool samples were eligible for further diagnostic tests, including sputum induction. Sputum samples were subjected to PCR for Cryptosporidium, as well as routine microbiology (culture and gram stain) and auramine stain for tuberculosis. Regression analyses were used to investigate 1) factors associated with respiratory cryptosporidiosis and 2) whether respiratory cryptosporidiosis was independently associated with hospitalization. Prevalence of enteric cryptosporidiosis was 260/1,918 (13.6%) (>80% Cryptosporidium hominis). Of the 236 children who had sputum available for analysis, 62 (26.3%) had Cryptosporidium in the sputum, only two of whom had HIV infection. Children with Cryptosporidium in the sputum were more likely to have abnormal oxygen saturation at presentation (SpO2 <96%; P = 0.053); no other differences in frequency or severity of respiratory signs were noted. No alternative bacterial cause of respiratory symptoms was identified in 37.7% of children with respiratory cryptosporidiosis, compared with 23.6% of children without (P = 0.04). Sputum-positive children had twice the odds of hospitalization compared with children without Cryptosporidium infection at this site (adjusted odds ratio = 2.08, 95% confidence interval: 1.02-4.22; P = 0.043). Respiratory tract involvement is common in children with intestinal cryptosporidiosis who are experiencing respiratory symptoms. Such children may experience some degree of respiratory compromise and may be at increased risk for hospitalization.Respiratory cryptosporidiosis is considered an occasional, late-stage complication of HIV/AIDS. This study aimed to assess the clinical importance of respiratory cryptosporidiosis in children with diarrhea and respiratory symptoms at Mulago Hospital, Kampala, Uganda. Children aged 9 to 36 months presenting with diarrhea and cough or unexplained tachypnea (N = 1,918) were screened for fecal Cryptosporidium using polymerase chain reaction (PCR). Children with positive stool samples were eligible for further diagnostic tests, including sputum induction. Sputum samples were subjected to PCR for Cryptosporidium, as well as routine microbiology (culture and gram stain) and auramine stain for tuberculosis. Regression analyses were used to investigate 1) factors associated with respiratory cryptosporidiosis and 2) whether respiratory cryptosporidiosis was independently associated with hospitalization. Prevalence of enteric cryptosporidiosis was 260/1,918 (13.6%) (>80% Cryptosporidium hominis). Of the 236 children who had sputum available for analysis, 62 (26.3%) had Cryptosporidium in the sputum, only two of whom had HIV infection. Children with Cryptosporidium in the sputum were more likely to have abnormal oxygen saturation at presentation (SpO2 <96%; P = 0.053); no other differences in frequency or severity of respiratory signs were noted. No alternative bacterial cause of respiratory symptoms was identified in 37.7% of children with respiratory cryptosporidiosis, compared with 23.6% of children without (P = 0.04). Sputum-positive children had twice the odds of hospitalization compared with children without Cryptosporidium infection at this site (adjusted odds ratio = 2.08, 95% confidence interval: 1.02-4.22; P = 0.043). Respiratory tract involvement is common in children with intestinal cryptosporidiosis who are experiencing respiratory symptoms. Such children may experience some degree of respiratory compromise and may be at increased risk for hospitalization. MEDLINE - Academic